Malignant Peripheral Nerve Sheath Scalp Tumor: A Short-Term Institutional Experience with Literature Review - Jha, Vikas Chandra; Alam, Mohammad Shahnawaz; Sinha, Vivek Saran (Asian Journal of Neurosurgery, 2023)
Malignant peripheral nerve sheath tumor (MPNST) of the scalp is rare. These lesions are associated with neurofibromatosis type 1 (NF1), but patients had been reported without NF1 also. We tried to analyze the difference between the clinical course and outcome of the patient with MPNST having stigmata of NF1 and without it. We included five patients treated over 3 years between July 2018 and July 2021 with diffuse scalp MPNST. Two of these five patients with MPNST of the scalp had neurocutaneous stigmata of NF1. Three were female and two males with an average age of 38.40 ± 18.48 years—the youngest with NF1 being a 19-year-old female. We found dull aching pain as the most typical complaint in all patients and a repeated episode of generalized seizure in one patient. In these cases, two patients with NF1 have highly vascular tumors and attained large sizes greater than 30 cm. These two cases required preoperative digital subtraction angiography (DSA) and embolization with n-butyl acrylate. Total excision of the tumor was done in all patients with radiotherapy. Metastases within 1 year were noted in two patients with NF1, and one of these two succumbed to her illness. The rest of the three patients without NF1 are under follow-up with no evidence of disease with a maximum follow-up of 2 years. Large MPNST (size > 20 cm) are rare and reported to have been associated with and without NF1. Patients with scalp MPNST with NF1 can achieve larger size with fast progression of tumor size and higher chances of recurrence and metastases.
Keywords: malignant peripheral nerve sheath tumor; diffuse scalp lesion; neurofibromatosis type 1; clinical course; treatment outcome